Cyclic shear test of a geosynthetic clay liner for a secondary containment application. Issue 2 (April 2010) - Athanassopoulos, C.; Fox, P.J.; Ross, J.D.
Abstract : ABSTRACT: This note presents the results of a cyclic shear test of a secondary containment liner system composed of sand/GCL/sand. The GCL was a needle-punch-reinforced woven/nonwoven product with a thin geomembrane laminated to the nonwoven side. Under a normal stress of 100 kPa, shearing occurred at the sand/geomembrane interface and the GCL sustained no visible damage after 25 cycles of loading with a displacement amplitude of 20 mm and a frequency of 1 Hz. Material property tests performed on pre-cyclic and post-cyclic GCL samples provided additional evidence that the GCL specimen did not sustain damage due to cyclic loading. Analysis of the cyclic loading data indicates hysteretic stress-displacement behavior that is broadly similar to natural soils and displays strength and stiffness degradation as well as reduction in damping ratio with continued cycling.